(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article reveals the content of new financial incentives for increasing the role of territorial communities in the formation of «green» economy in Ukraine, since the existing financial forms of the implementation of the climatic tasks set for our country in international environmental agreements do not yet produce adequate results. For this purpose, the experience of developed countries on this issue is analyzed and ways of its use in Ukraine are offered. The emphasis is on the forms of use of «green» finance used in the countries of the European Union, as our country has chosen the path of European integration. The article analyzes both the positive aspects of the use of separate components of «green» finance in Ukraine at the regional and local levels, as well as the problems existing here. First of all, it concerns the inefficient use of forest resources that contribute to the absorption of most of the greenhouse gases. It is emphasized on the necessity of the comprehensive consideration of both the central Ukrainian authorities and the territorial authorities, the requirements of the European Union environmental legislation, so that our state can receive «green» investments from it. It is stressed that the Ukrainian state has not yet created the right conditions for the territorial communities to introduce a «green» economy in their territories, so the united territorial communities try to find on their own unconventional forms of solving this problem. First of all, it concerns the use of renewable energy sources, including biowaste. The ways of improving the application of separate components of «green» finance both at the regional and local levels, primarily at the level of the united territorial communities, are grounded. The directions of improvement of cooperation with foreign investors, which would help the territorial communities of our country to attract foreign investments from private structures, as well as from international financial institutions, in particular from the Green Climate Fund and other environmental funds, are offered.